1993
DOI: 10.1016/0360-3016(93)90416-s
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of human chorionic gonadotropin-producing seminoma treated by postoperative radiotherapy

Abstract: Based on this series of patients, human chorionic gonadotropin production is not an unfavorable prognostic factor in pure seminoma. Even in the subgroups with high or very high human chorionic gonadotropin levels (who had a higher proportion of advanced stages), the prognosis remained excellent. In Stage I and IIA seminoma with abnormal human chorionic gonadotropin levels, recurrence rate after post-operative radiotherapy alone is extremely low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
2
8
0
4
Order By: Relevance
“…Our data confirm the results of other authors who found higher stages in seminomas with HCG or LDH elevations [1, 24, 25]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data confirm the results of other authors who found higher stages in seminomas with HCG or LDH elevations [1, 24, 25]. …”
Section: Discussionsupporting
confidence: 83%
“…Nearly all reports were based on small, retrospectively documented series. Only the retrospective analysis of Mirimanoff et al [25]attained 132 HCG-positive cases from ten centers in Switzerland. Schwartz et al [33]reported on 191 stage I seminomas that could be completely reviewed, retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…During the first year of the study, only patients with negative presurgical levels of b-HCG were admitted. During the second and third year of the trial, patients with elevated b-HCG levels of up to 200 IU l À1 were admitted as well, once there was evidence that initial b -HCG elevation did not adversely affect the prognosis of the patients (Mirimanoff et al, 1993). Exclusion criteria were a positive AFP level prior to orchiectomy, a history of prior abdominal/pelvic radiotherapy or chemotherapy, withdrawal of informed consent, concurrent severe diseases, or treatment with cobalt-60 machines.…”
Section: Patient Selection and Staging Processmentioning
confidence: 99%
“…During the first year of the study, only patients with negative pre-operative levels of ß-hCG were admitted to the study. During the second and third years of the trial, patients with raised ß-hCG levels of up to 200 IU/l were admitted as well since 2 reports have suggested that prognosis is not affected by initial ß-hCG levels (Mirimanoff et al, 1993;Weissbach and BussarMaatz, 1993). Furthermore, no history of prior radiotherapy or chemotherapy or concurrent severe illness was allowed for entry into the study.…”
Section: Patient Selection and Staging Proceduresmentioning
confidence: 99%